Use of Play Therapy in Nursing Process: A Prospective Randomized Controlled Study - KADIOĞLU, HASİBE (WILEY, 2017)
Purpose: Play therapy is a nursing intervention employed in multidisciplinary approaches to develop the social, emotional, and behavioral skills of children. In this study, we aim to determine the effects of play therapy on the social, emotional, and behavioral skills of pre-school children through the nursing process. Design: A single-blind, prospective, randomized controlled study was undertaken. The design, conduct, and reporting of this study adhere to the Consolidated Standards of Reporting Trials (CONSORT) guidelines. Methods: The participants included 4-to 5-year-old kindergarten children with no oral or aural disabilities and parents who agreed to participate in the study. The Pre-school Child and Family Identification Form and Social Competence and the Behavior Evaluation Scale were used to gather data. Games in the play therapy literature about nursing diagnoses (fear, social disturbance, impaired social interactions, ineffective coping, anxiety), which were determined after the preliminary test, constituted the application of the study. Findings: There was no difference in the average scores of the children in the experimental and control groups in their Anger-Aggression (AA), Social Competence (SC), and Anxiety-Withdrawal (AW) scores beforehand (t = 0.015, p =.988; t = 0.084, p =.933; t = 0.214, p =.831, respectively). The difference between the average AA and SC scores in the post-test (t = 2.041, p =.045; t = 2.692, p =.009, respectively), and the retests were statistically significant in AA and SC average scores in the experimental and control groups (t = 4.538, p =.000; t = 4.693; p =.000, respectively). In AW average scores, no statistical difference was found in the post-test (t = 0.700, p =.486), whereas in the retest, a significant difference was identified (t = 5.839, p =.000). Conclusions: Play therapy helped pre-school children to improve their social, emotional, and behavioral skills. It also provided benefits for the children to decrease their fear and anxiety levels, to improve their communication and coping skills, and to increase their self-esteem. Clinical Relevance: The study concluded that play therapy helps develop the social, emotional, and behavioral skills of pre-school children. It has also helped children lower their fear and anxiety levels, improve their communication and coping skills, and promote their self-esteem. Pediatric nurses are recommended to include play therapy in their profession and in the nursing process.
Keywords: Nursing intervention; nursing process; play therapy; pre-school children; PRESCHOOL-CHILDREN; SOCIAL COMPETENCE; ANXIETY; SCHOOLS